Group generated analogical drawings in biology effects on students' social regulation, critical reflection, and scientific reasoning skills - Manosca, Leogiver G. (College of Education, University of the Philippines Diliman, 2019)
The purpose of this study was to investigate the effects of group-generated analogical drawing teaching approach on students' social regulation, critical reflection, and scientific reasoning skills. This study utilized two-group pretest-posttest quasi-experimental research design that includes two Grade 10 classes in a science high school in Caloocan during the School Year 2017-1018. Prior to the intervention, the two intact classes were randomly assigned to either the Group-Generated Analogical Drawing Teaching Approach (GGADTA) or the Conventional Teaching Approach (CTA). The intervention lasted from November 2017 to January 2018. Using the following instruments as pretest and posttest during the 3rd quarter Living Things and their Environment Unit of Science 10-Social Regulation in Group Work Scale (SRGWS) for social regulation skills (SRS), the Critical Reflection Inventory Self-Report Scale (CRISRS) for critical reflection skills (CRS), and Lawson Classroom Test of Scientific Reasoning (LCTSR) for Scientific Reasoning Skills (ScRS)-results showed that the students exposed to group-generated analogical drawing teaching approach have a significant higher posttest mean score in the social regulation skills particularly in the planning dimension of SRGWS than those who were exposed to the convention teaching approach. No significant improvement was observed for the critical reflection skills and scientific reasoning skills. Also, social regulation skills and critical reflection skills are moderately positively correlated, while social regulation skills and scientific reasoning skills are not correlated. Lastly, it was found that critical reflection skills do not predict scientific reasoning skills.